Rock Art Dating and the Peopling of the Americas. (23rd May 2013) - Whitley, David S.
Abstract : The peopling of the Americas is both the oldest and most frequently researched question in American archaeology. Although rarely considered, early art has the potential to provide insight into questions that may be obscured by other kinds of evidence, particularly stone tools. What part did art play in the peopling of the Americas? This question is addressed starting with a reconsideration of rock varnish chronometrics as applied to Great Basin, eastern California, petroglyphs. This demonstrates, conservatively, that the petroglyph tradition began before 11, 100 YBP, probably before 12, 600 YBP, and potentially in the 14, 000 years range. Comparison of these ages with evidence from other regions in the hemisphere demonstrates substantial artistic and stylistic variation in rock art by the Paleoindian period (circa 10, 000–11, 000 YBP). This suggests that, while art may have been part of the baggage of the first immigrants, regional cultural traditions had already been developed by the Terminal Pleistocene, if not earlier. The result is evidence for the development of regional cultural diversity in the Americas by Paleoindian times.